ENGOT-en11/GOG-3053/KEYNOTE-B21: a randomised, double-blind, phase III study of pembrolizumab or placebo plus adjuvant chemotherapy with or without radiotherapy in patients with newly diagnosed, high-risk endometrial cancer - Van Gorp, T; Cibula, D; Lv, W; Backes, F; Ortaç, F; Hasegawa, K; Lindemann, K; Savarese, A; Laenen, A; Kim, Y M; Bodnar, L; Barretina-Ginesta, M-P; et al. (Annals of oncology, 2024)
BACKGROUND: Pembrolizumab plus chemotherapy provides clinically meaningful benefit as first-line therapy for advanced (locoregional extension and residual disease after surgery)/metastatic/recurrent mismatch repair-proficient (pMMR) and mismatch repair-deficient (dMMR) endometrial cancer, with greater magnitude of benefit in the dMMR phenotype. We evaluated the addition of pembrolizumab to adjuvant chemotherapy (with/without radiation therapy) among patients with newly diagnosed, high-risk endometrial cancer without any residual macroscopic disease following curative-intent surgery. METHODS: We included patients with histologically confirmed high-risk [International Federation of Gynecology and Obstetrics (FIGO) stage I/II of non-endometrioid histology or endometrioid histology with p53/TP53 abnormality, or stage III/IVA of any histology] endometrial cancer following surgery with curative intent and no evidence of disease postoperatively, with no prior radiotherapy or systemic therapy. Patients were randomised to pembrolizumab 200 mg or placebo every 3 weeks (Q3W) for six cycles added to carboplatin-paclitaxel followed by pembrolizumab 400 mg or placebo every 6 weeks (Q6W) for six cycles per treatment assignment. Radiotherapy was at the investigator's discretion. The primary endpoints were investigator-assessed disease-free survival (DFS) and overall survival in the intention-to-treat population. RESULTS: A total of 1095 patients were randomised (pembrolizumab, n = 545; placebo, n = 550). At this interim analysis (data cut-off, 4 March 2024), 119 (22%) DFS events occurred in the pembrolizumab group and 121 (22%) occurred in the placebo group [hazard ratio 1.02, 95% confidence interval (CI) 0.79-1.32; P = 0.570]. Kaplan-Meier estimates of 2-year DFS rates were 75% and 76% in the pembrolizumab and placebo groups, respectively. The hazard ratio for DFS was 0.31 (95% CI 0.14-0.69) in the dMMR population (n = 281) and 1.20 (95% CI 0.91-1.57) in the pMMR population (n = 814). Grade ≥3 adverse events (AEs) occurred in 386 of 543 (71%) and 348 of 549 (63%) patients in the pembrolizumab and placebo groups, respectively. No treatment-related grade 5 AEs occurred. CONCLUSIONS: Adjuvant pembrolizumab plus chemotherapy did not improve DFS in patients with newly diagnosed, high-risk, all-comer endometrial cancer. Preplanned subgroup analyses for stratification factors suggest that pembrolizumab plus chemotherapy improved DFS in patients with dMMR tumours. Safety was manageable. TRIAL REGISTRATION: ClinicalTrials.gov, NCT04634877; EudraCT, 2020-003424-17. RESEARCH SUPPORT: Merck Sharp & Dohme LLC, a subsidiary of Merck & Co., Inc., Rahway, NJ, USA.
Keywords: nádory endometria; dospělí; Female; Adult; ženské pohlaví; adjuvantní chemoterapie; lidé; dvojitá slepá metoda; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Double-Blind Method; Aged; Chemotherapy, Adjuvant; lidé středního věku; humanizované monoklonální protilátky; senioři nad 80 let; Endometrial Neoplasms; senioři; Antibodies, Monoclonal, Humanized; Middle Aged; Humans